O direito à educação no Brasil sob a lente da teoria crítica dos direitos humanos: antinomias entre os efeitos da juridicização e a efetivação mais substantiva desse direito - Arantes, Evandro Borges (Universidade Federal do Tocantins, 2016)
This dissertation is linked to "research line 2" (jurisdictional Instruments, access to justice and human rights) of the Professional and Interdisciplinary Master's Program in Human Rights and Jurisdictional Provision-MPIPJDH, focusing research on the analysis of the effectiveness of these rights in the context of guardianship offered by jurisdictional instruments. The general objective is to understand the process of juridicização of the human right to education and its drift in relation to substantive claim that right, what unfolds in four specific objectives: Identify the generating situation of the growing juridicização of the right to education in Brazil; Check the effects of the juridicização with regard to this law; Assess to what extent the legislative overproduction and the judicial activism harm facing systemic educational problems; Demonstrate that the spaces of representation and social control already in place, if they are appropriate for the exercise of popular sovereignty, are alternatives preferable to juridicização. About the theoretical framework, the Coupe research on critical theory of human rights, molded into the Frankfurt School, which provides a multi-dimensional view of the right to education, stating that the implementation of that right should take place via social empowerment, because the juridicizada carries risks and ideological tutelage inhibits effective full collective's rights. As a result, are explained the methodological path, emphasizing that this is a desk research, qualitative and exploratory type, focused on analysis of explicit and implicit content of bills and symptomatic of the process of court decisions juridicização. In the empirical approach to the problem, from the systematization of the impressions collected, the guiding questions of the survey are responses that allow point, conclusively, alternative routes to the juridicização so that the right to education is effective in Brazil of plural and democratic mode, making the country a privileged space of free expression of its citizens.